Inhibition of the pqsABCDE and pqsH in the pqs quorum sensing system and related virulence factors of the Pseudomonas aeruginosa PAO1 strain by farnesol. (July 2020) - Li, Wen-Ru; Zeng, Tao-Hua; Xie, Xiao-Bao; Shi, Qing-Shan; Li, Cai-Ling
Abstract: Farnesol, a 15-carbon, naturally occurring sesquiterpene alcohol, exists widely in plants and Candida albicans . It inhibits the production of the Pseudomonas Quinolone Signal (PQS) and pyocyanin of the opportunistic pathogen Pseudomonas aeruginosa, but the underlying mechanisms remained unknown. In this study, the actions of farnesol on the growth, production of virulence factors (including PQS signals, elastase, pyocyanin, biofilm, and swarming motility), and the transcription of some essential key genes of three Quorum Sensing (QS) systems and other related virulence genes in the P. aeruginosa PAO1 strain were investigated. Moreover, the qRT-PCR and high throughput transcriptome/proteome sequencing techniques were used to differentiate the transcriptomic/proteomic expressions of the PAO1 strain following farnesol exposure. The experimental results showed that farnesol did not inhibit PAO1 growth or affect its elastase production. However, farnesol did suppress the transcription and protein expression of the pqsABCDE and pqsH genes in the strain's pqs QS system and then inhibit the PQS production, while leaving the transcription and protein expression of pqsR in the pqs system, of lasI and lasR in the las QS system, and of rhlI and rhlR in the rhl QS system unaffected. Farnesol also inhibited the expression of some related virulence genes and the production of the related virulence factors. For example, it inhibited the protein expression of key genes in the phenazine biosynthesis pathway, including key genes related to pyocyanin synthesis ( phzM, phzS), inhibiting the strain's capacity for biofilm formation. In addition, farnesol enhanced the transcription and protein expression of key genes in the geraniol degradation pathway. Farnesol also stimulated the PAO1 strain with regard to swarming motility. As a result, we concluded that farnesol can suppress the virulence by inactivating the pqs QS system in pathogen P. aeruginosa, which would be significant to develop a kind of effective drug control the virulence and pathogenesis of this bacteria. Highlights: Farnesol inhibited the pqsABCDE and pqsH genes in the pqs system of the PAO1 strain. Farnesol inhibited the PQS production of the PAO1 strain. The pqsR, lasI / lasR, and rhlI / rhlR in the QS system of the PAO1 strain were not inhibited by farnesol. Farnesol inhibited some related virulence genes and the virulence factors. Farnesol stimulated the PAO1 strain with regard to swarming motility.